Observational evidence of herbivore‐specific associational effects between neighboring conspecifics in natural, dimorphic populations of Datura wrightii - Goldberg, Jay K. (John Wiley and Sons Inc., 2021)

(untitled) (Ecol Evol)
Associational effects—in which the vulnerability of a plant to herbivores is influenced by its neighbors—have been widely implicated in mediating plant–herbivore interactions. Studies of associational effects typically focus on interspecific interactions or pest–crop dynamics. However, associational effects may also be important for species with intraspecific variation in defensive traits. In this study, we observed hundreds of Datura wrightii—which exhibits dimorphism in its trichome phenotype—from over 30 dimorphic populations across California. Our aim was to determine whether a relationship existed between the trichome phenotype of neighboring conspecifics and the likelihood of being damaged by four species of herbivorous insects. We visited plants at three timepoints to assess how these effects vary both within and between growing seasons. We hypothesized that the pattern of associational effects would provide rare morphs (i.e., focal plants that are a different morph than their neighbors) with an advantage in the form of reduced herbivory, thereby contributing to the negative frequency‐dependent selection previously documented in this system. We found the best predictor of herbivory/herbivore presence on focal plants was the phenotype of the focal plant. However, we also found some important neighborhood effects. The total number of plants near a focal individual predicted the likelihood and/or magnitude of herbivory by Tupiochoris notatus, Lema daturaphila, and Manduca sexta. We also found that velvety focal plants with primarily sticky neighbors are more susceptible to infestation by Tupiochoris notatus and Lema daturaphila. This does not align with the hypothesis that associational effects at the near‐neighbor scale contribute to a rare‐morph advantage in this system. Overall, the results of our study show that the number and trichome‐morph composition of neighboring conspecifics impact interactions between D. wrightii and insect herbivores.